Faktor yang Berhubungan dengan Ketepatan Pelaksanaan Triase Modern Canadian Triage Acquity System (CTAS) - Yeni Devita; Mutiara Pertiwi; Wardah; Pratiwi Gasril (Sistem Informasi, 2023)
Some patients who visit the Emergency Department (IGD) are not in an emergency condition, one way to sort it out is by triage. There are still many hospitals that are not appropriate in implementing triage, increasing the risk of death and disability of emergency patients. The purpose of this study was to determine the factors related to the accuracy of the implementation of modern triage CTAS. This research was conducted at the IGD of Bengkalis Regional Hospital. The total population is 20 emergency room nurses, with sampling using the total sampling technique. The analysis used is frequency distribution and chi square statistical test. The results of this study concluded that: Ada significant relationship between the level of knowledge of nurses and the accuracy of the implementation of the Modern Triage of the CTAS system (p value 0.002); Ada significant relationship between nurse skills and the accuracy of the implementation of the Modern Triage of the CTAS system (p value 0.011); Ada significant relationship between the perception of nurse workload and the accuracy of the implementation of the Modern Triage of the CTAS system (p value 0.00 0); Ada significant relationship between the length of work of the nurse and the accuracy of the implementation of the Modern Triage of the CTAS system (p value 0.003); Asignificant relationship between nurse training and the accuracy of the implementation of the Modern Triage CTAS system (p value 0.033). This study recommends improving the competence of all emergency room nurses, particularly through BTCLS training and modern triage of the CTAS system.